2023
DOI: 10.1002/jclp.23585
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationship between child maltreatment, bullying victimization, depression, and nonsuicidal self‐injury among left‐behind children in China: 2‐year follow‐up

Ru Yan,
Wan Ding,
Die Wang
et al.

Abstract: BackgroundLeft‐behind childre (LBC) in China are deeply concerned by society because of their high risk of emotional and behavioral problems. Depression and nonsuicidal self‐injury are the most harmful and worrying negative emotional and behavioral problems in LBC. Unfortunately, LBCs are in unfavorable environments for a long time and are prone to negative interpersonal interactions. Child maltreatment and bullying victimization, as the two most typical negative interpersonal interactions in family and school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…School climate refers to the quality and characteristics of school life, encompassing teacher support, peer support, and opportunities for autonomy, emphasizing the interpersonal relationships among students and between students and teachers [41]. A positive school climate signi cantly promotes the psychological and behavioral development of left-behind children [42], providing them with a sense of security and emotional support, thus reducing the occurrence of adverse emotions [43]. Studies have found a signi cant negative correlation between school climate and adolescent depression; adolescents who perceive a school climate as negative are more prone to experiencing depressive issues [44][45][46].…”
Section: The Moderating Role Of School Climatementioning
confidence: 99%
“…School climate refers to the quality and characteristics of school life, encompassing teacher support, peer support, and opportunities for autonomy, emphasizing the interpersonal relationships among students and between students and teachers [41]. A positive school climate signi cantly promotes the psychological and behavioral development of left-behind children [42], providing them with a sense of security and emotional support, thus reducing the occurrence of adverse emotions [43]. Studies have found a signi cant negative correlation between school climate and adolescent depression; adolescents who perceive a school climate as negative are more prone to experiencing depressive issues [44][45][46].…”
Section: The Moderating Role Of School Climatementioning
confidence: 99%
“…Although the study is not focused on LBC, it is reasonable to infer that LBC may be more susceptible to sexual abuseprovoked depression [49,51,52]. Additionally, family factors can affect LBC's psychological symptoms, including family income [53] parental education [54], and rearing patterns [55]. For example, A research showed that a low family income level was positively associated with severe DS among LBC, speci cally, family income below 2,000 RMB per month presented a risk of major DS that was 4.02 times greater than that in homes with a monthly income above 8,000 RMB [56].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, psychological health problems and their risk factors among LBC urgently require close attention. Furthermore, most research has determined that individual lifestyle, school social environment, and family factors are strongly associated with DS and AS among LBC [53,54], but only a few studies have examined the relationship between left-behind characteristics and DS and AS among LBC [60,61]. We argue, however, that different types of caregivers, parent-child separation timing, and the duration of parent-child separation may have far-reaching in uence on DS and AS among LBC.…”
Section: Introductionmentioning
confidence: 99%
“…However, cyberbullying is characterized by anonymity, uncertain audiences and the potential to occur anytime and anywhere (Låftman et al, 2017). Bullying is widespread among groups of children and often results in negative consequences, including anxiety (Pontillo et al, 2019), depression (Yan et al, 2023) and suicidal tendencies (Dehnel et al, 2023). Therefore, scholars must explore the factors related to bullying to develop better prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying is a form of aggressive behaviour through physical and electronic means in which someone intentionally and repeatedly causes another person injury or discomfort (Chu et al, 2023; Yan et al, 2023). Bullying includes both traditional and cyber forms, and they are repetitive, intentionally hurtful and characterized by power imbalance.…”
Section: Introductionmentioning
confidence: 99%